PRODUCTION AND RICE FARMING INCOME IN THE LEBAK LANDS OGAN KOMERING ILIR DISTRICT, SOUTH SUMATERA - Suparwoto, Suparwoto (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The activity was carried out in the Awal Terusan village, Sirah Pulau Padang Subdistrict, Ogan Komering Ilir Regency, South Sumatra starting in the dry season of 2017. The purpose of the activity is to find out the production and income of superior varieties of rice farming on lebak land. The varieties used are: Inpari 9, Inpari 30, Inpari 33, Inpara 4 and Mekongga, IR 42 as a comparison of one hectare. Spacing of Legowo 2: 1 (50 cm x25 cm x 12.5 cm). The dosage of fertilizer is 150 kg / ha urea, 100 kg / ha TSP and 100 kg / ha KCL are distributed. The method used is direct observation on the field of superior varieties exhibited. The data obtained was arranged in tabulation and analyzed by statistical tests, namely the test of the mean value (test-t) and farm analysis. The results showed that the plant height of Inpari 9, Inpari 30, Inpari 33 and Inpara 4 were low so that they were suitable for planting on lebak lands. Productivity of Inpari 9 and Inpara 4 are higher than Mekongga and IR 42, which are 7.6-7.7 tons GKP / ha, while the productivity of Inpari 33 and Inpari 30 is 3.8-4.4 tons GKP / ha lower than Mekongga and IR 42. Economically rice farming using all varieties is profitable except Inpari 33, but income Inpari 9 and Inpara 4 are greater than other varieties with BC ratio 3.5 and 2.5.